Comparison Of The Effects Of Ivermectin, Permethrin & Gamma Benzene Hexachloride Alone And With That Of Combination Therapy For The Management Of Scabies.: Effect and Safety of Scabicidal drugs - Saborni Dey; Sachin Agarwal; Sagar (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
ABSTRACT : The present study compared three scabicidal agents alone or with combination - the currently considered medicine of choice permethrin, oral ivermectin and gamma benzene hexachloride in the local population of India. A total of 120 patients were enrolled and randomly divided into 4 groups. Group A received topical 5% permethrin & oral placebo, Group B was given topical placebo cream & oral ivermectin in two dose regimen. Group C received topical 1% gamma benzene hexachloride with oral placebo & Group D was given topical 5% permethrin & oral ivermectin. The improvement of lesions & pruritus were assessed in the next 3 follow ups i.e. at the 7th day, 14th day, & 28th day along with any adverse drug reactions (ADRs). Group A had 83%, 90%, 97% while Group B had 70%, 81% & 91% improvement of lesions in 3 follow ups. Group C showed 57%, 70%, 86% and Group D had 82%, 90%, 97% efficiency to decrease lesion count.(p>0.05) Again Group A observed 77%, 88%, 94% improvement in pruritus in subsequent follow ups, while for Group B it was 63%, 76% & 86%. Group C had 55%, 71%, 85% efficiency and Group D had recorded 77%, 88% & 94% improvement to decrease pruritus.(p>0.05) The incidence of adverse effects was found to be less in Group B, Group C & Group D when compared to Group A. Conclusion : Group D or combination therapy was a better choice for scabies in comparison to other monotherapy due to its better efficacy and safety profile. Keywords : Scabies, permethrin, ivermectin, gamma benzene hexachloride.